Long‐term feasibility and biocompatibility of directly microsurgically implanted intrafascicular electrodes in free roaming rabbits. Issue 2 (19th April 2018) - Zhen, Gehua; Chen, Huanwen; Tsai, Shin‐Yi; Zhang, Jian; Chen, Tongyi; Jia, Xiaofeng
Abstract: Novel neural interfaces capable of reliably capturing electrical signals are crucial for the development of prostheses. Longitudinal intrafascicular electrodes (LIFEs) have been proposed as a promising technology, and their feasibility and biocompatibility need to be investigated for long‐term implantation. In this study, custom‐designed 95%Pt–5%Ir intrafascicular electrodes were implanted into the sciatic nerves of 14 rabbits using our novel direct microsurgical technique. The biocompatibility and their ability to record electrophysiological signals were serially investigated up to 9 months after implantation. Nerve tissues were examined using light and transmitted electron microscopy, and axon diameters were quantified, evaluated over time, and compared with sham‐control ( N  = 4). Selective stimulation and stable recording properties of electrical signals were achieved by intrafascicular electrodes along the experimental period. While electrophysiological signal amplitude decreased by as early as 1 month after implantation ( p  < 0.05), the signal strength recovered to baseline levels by 3–5 months ( p  > 0.05). Axon diameter results showed a similar trend of initial decline (10.8% reduction, p  < 0.01) followed by gradual recovery by 6 months ( p  > 0.05). Microstructural and ultrastructural analysis revealed modest tissue damage at the implantation site after implantation with gradual normalization over time. Intrafascicular electrodes implanted with direct microsurgical techniques demonstrated good biocompatibility and have great potential for long‐term implantation and electrophysiological recordings. Though subtle tissue damage impaired ability to capture electrophysiological signals in the first 2 months, this damage gradually normalized after 3 months, and was fully normalized by 6 months. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 435–444, 2019.